Effectiveness of Empowering Pregnant Women on Body Image During Pregnancy in the Working Area of Bunga Jadi Health Center - Eva Pebrianti; Dwi Prihatin Era; Cristinawati Haloho (PT FORMOSA CENDEKIA GLOBAL, 2023)
Psychological changes in pregnant women can become a mental health problem. In Indonesia, 75% are worried about body image during pregnancy and 20% are depressed about their body shape during pregnancy. Preliminary studies at the Bunga Jadi Health Center in January-November 2022 found 371 pregnant women and initial interviews with 5 pregnant women found that they experienced disturbances in body image changes. This type of research is quasi-experimental, non-equivalent control group design. The population is all pregnant women in the working area of the Bunga Jadi Health Center for January-November 2022 a total of 371 people. Lameshow formula, so that the sample of the intervention group is pregnant women who are given empowerment of pregnant women (mental health education 2 meetings within 3 weeks, pregnancy exercise class 2 meetings within 3 weeks and use of VCO 2 times a day after bathing as much as 2 ml for each topical within 3 weeks) and the control group, namely pregnant women from regular exercise classes, each numbering 41 people